2019
DOI: 10.1093/bib/bbz113
|View full text |Cite
|
Sign up to set email alerts
|

Identification and comprehensive characterization of lncRNAs with copy number variations and their driving transcriptional perturbed subpathways reveal functional significance for cancer

Abstract: Numerous studies have shown that copy number variation (CNV) in lncRNA regions play critical roles in the initiation and progression of cancer. However, our knowledge about their functionalities is still limited. Here, we firstly provided a computational method to identify lncRNAs with copy number variation (lncRNAs-CNV) and their driving transcriptional perturbed subpathways by integrating multidimensional omics data of cancer. The high reliability and accuracy of our method have been demonstrated. Then, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 54 publications
0
9
1
Order By: Relevance
“…Therefore, tumor patients were divided into a group with CNV in the lncRNA and a control group based on lncRNA copy number profiles. Moreover, lncRNAs tended to undergo overall copy number amplification in LUSC ( Figure 1B ), which is contrary to a previous study suggesting that copy number deletion pattern of the lncRNAs was widely observed in various cancer types ( Xu et al, 2020 ). Furthermore, we identified 372 lncRNAs whose expression levels (FPKM) are driven by CNV ( Figure 1C ).…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Therefore, tumor patients were divided into a group with CNV in the lncRNA and a control group based on lncRNA copy number profiles. Moreover, lncRNAs tended to undergo overall copy number amplification in LUSC ( Figure 1B ), which is contrary to a previous study suggesting that copy number deletion pattern of the lncRNAs was widely observed in various cancer types ( Xu et al, 2020 ). Furthermore, we identified 372 lncRNAs whose expression levels (FPKM) are driven by CNV ( Figure 1C ).…”
Section: Resultscontrasting
confidence: 99%
“…Genetic variation in the lncRNA region, such as single-nucleotide variation, somatic mutation, and copy number variation (CNV), may affect the expression level of the gene and its target genes, which may contribute to tumor occurrence and development ( Wang et al, 2020 ). For example, lncRNAs with CNVs drive transcriptional perturbed functional pathways ( Xu et al, 2020 ), and single-nucleotide variation in lncRNA regulates cancer-related pathways through ceRNA mechanism ( Zhang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs are known to sometimes originate from transposable elements (TEs) (Zhu et al, 2022; Kapusta et al, 2013), yet what implications this has for their expression, epigenetics and variation is not well known. Similarly, while aberrant lncRNA copy number has been connected to disease and other phenotypes (Xu et al, 2020; Athie et al, 2020), general information about lncRNA copy number and its consequences is missing, in particular in plants.…”
Section: Introductionmentioning
confidence: 99%
“…LncRNA ST7-AS1 is a newly discovered one located on 7q31.2 (Qin et al, 2019). LncRNA ST7-AS1 with Copy Number Variations (CNVs) can cause gene disorder in downstream cancers, which is also strongly linked to proliferation, apoptosis, and cell migration belonging to the biological processes of cancer (Xu et al, 2019). Based on current evidence, ST7-AS1 has a strong correlation with human glioma and laryngeal squamous cell carcinoma (Liu et al, 2015;Tian et al, 2017).…”
Section: Introductionmentioning
confidence: 99%